GOVERNANCE, WORK SCOPE AND BUDGET FOR SECURITY AND SAFETY WITHIN THE PROJECT MANAGEMENT OF THE SUMMER OLYMPIC GAMES FROM SYDNEY 2000 TO TOKYO 2021: COMPARATIVE ANALYSIS AND FUTURE PERSPECTIVES - Leško, Luka (Digital Repository of Theses, 2022)
The Olympic Games require one of the most complex mass event-related security operations in the world. Security and safety became one of the most important (and the most expensive) parts within the project management of the Olympics. Using both theoretical and empirical knowledge, this research on governance, work scope and budget for security and safety within the project management of the summer Olympic Games from Sydney 2000 to Tokyo 2021 (six case studies) provides a comparative analysis and future perspectives in the domain of Olympics-related security and safety. Alongside risk evolution, each of the following Olympic Games are more complex, which indicates the general failure of society to gradually make life safer. This confirms the basic determinants of security studies - constantly expanding and deepening. Counter-terrorism is significantly more expensive than terrorism itself. Although it is suppressed by large investments in vi security, terrorism remains the greatest threat to the Olympics due to the scale of direct (human fatalities and property damage) and indirect effects (public fear and anxiety). Cyber-attacks, in which damage can be done without the physical presence of the perpetrator, are becoming an extremely threat to the Olympics. The evolution of risk has conditioned the CERT to be an indispensable part of the security preparation of the Olympics. Due to the drastic increase in the security capacity of the Olympics, no realized major security incidents were recorded from 2000 to 2021. In terms of governance, evolution from domicile to international multi-agency cooperation and evolution of the number of stakeholders involved suggest that each subsequent Olympic Games are more complex. Although the security budget occupies a significant share of the total organizational budget of the Games (post-9/11 security budget is no longer measured in millions but in billions USD), those investments can be justified by long-term legacy in terms of urban development, personnel, technology, governmental policies, etc. Further research should address the methods to optimize security measures against restrictions of human rights and liberties. In addition to deepening theoretical and empirical studies of counterterrorism, further research on prevention of inter-agency rivalry as well as prevention of cyber-attacks at the Olympic Games is recommended.